Sperm quality of artificially matured shortfinned eel is not affected by human chorionic gonadotropin dose and route of administration - Divers, Sean L.; Johnson, Sheri L.; Lokman, P. Mark (PeerJ, 2022)
Background Acquisition of high quality sperm is key to the artificial propagation of eels in captivity, but fertility drugs are expensive and repeated handling is stressful to the fish. An interrupted treatment regime (an initial hormone injection to stimulate spermatogenesis, followed several weeks later by weekly booster injections to induce sperm maturation) for acquisition of sperm in captive male eels has promise for high sperm quality on the one hand, and animal welfare benefits on the other. To further develop this approach for shortfinned eel, Anguilla australis, we evaluated the efficacy of (i) different initial doses of human chorionic gonadotropin (hCG) and (ii) route of administration. Methods Male eels were artificially induced to mature with a single injection of 0, 250, 500 or 1,000 IU/fish of hCG, administered either intramuscularly (IM) or intraperitoneally (IP). Sperm maturation was induced with 150 IU hCG/fish from week 5 onwards and sperm collected for evaluation of quality by computer-assisted sperm analysis. Results Control males did not mature and hence, sperm could not be retrieved and analysed, but all other treatments were effective in inducing testicular maturation. Milt volume tended to be higher for fish injected IM compared to those injected IP, whereas hCG dose had no effect. Conversely, the concentration of spermatozoa tended to be higher for several sperm collection time points in IP-injected than in IM-injected fish. Sperm quality, represented by percent motility, percent progressive motility and curvilinear velocity, was equal in fish given an initial dose of 250 IU hCG to those given higher initial doses of hCG. Conclusions We recommend that an initial dose of 250 IU hCG/fish be administered to induce spermatogenesis in male A. australis, and, after a period of 4–5 weeks, weekly booster injections of ∼150 IU hCG/fish be administered in the day prior to sperm collection; both routes of administration (IM or IP) are equally effective. We contend that an interrupted treatment regime has notable benefits for induced maturation in male anguillids, as it reduces fish handling and manipulation and reduces the resources required to produce high quality sperm.
Keywords: Sperm quality; CASA; Human chorionic gonadotropin; Motility; Eel; Anguilla; Dosage; Route of administration